Relaciones ciencia-tecnología-sociedad en la educación científica colombiana: una revisión del estado de la cuestión (2017-2021) - Alvarez-Tobón, Yisneth-Nathaniela; Arroyave-Giraldo, Dora-Inés; García-Carmona, Antonio (Revista Científica, 2021)
This article presents the results of a documentary research whose objective was to analyze the trends on the approach to science-technology-society (STS) relationships in science education in Colombia between 2017 and 2021. To this effect, a qualitative methodology was used, which was based on the discursive textual analysis of the selected documents with the help of the Nvivo11 software. The analysis categories were: type of study, methodology, population, STS didactic context, and incorporation of STS relationships in science education. Among other results, a recurrent use of history and epistemology of science was observed, as well as the use of scientific controversies to address STS relationships in science education within the Colombian context.